Value co-production: intellectual origins and implications for practice and research - Ramírez, Rafael (Strategic Management Journal, 1999)
This paper surveys the history of an alternative view of value creation to that associated with industrial production. It argues that technical breakthroughs and social innovations in actual value creation render the alternative—a value co-production framework—ever more pertinent. The paper examines some of the implications of adopting this framework to describe and understand business opportunity, management, and organizational practices. In the process, it reviews the research opportunities a value co-production framework opens up. Copyright © 1999 John Wiley & Sons, Ltd.